Microphysical properties and radiative impact of an intense biomass burning aerosol event measured over Ny-Ålesund, Spitsbergen in July 2015. Issue 1 (1st January 2018) - Ritter, C.; Angeles Burgos, M.; Böckmann, C.; Mateos, D.; Lisok, J.; Markowicz, K.M.; Moroni, B.; Cappelletti, D.; Udisti, R.; Maturilli, M.; Neuber, R.
Abstract: In this work, an evaluation of an intense biomass burning event observed over Ny-Ålesund (Spitsbergen, European Arctic) in July 2015 is presented. Data from the multi-wavelengths Raman-lidar KARL, a sun photometer and radiosonde measurements are used to derive some microphysical properties of the biomass burning aerosol as size distribution, refractive index and single scattering albedo at different relative humidities. Predominantly particles in the accumulation mode have been found with a bi-modal distribution and dominance of the smaller mode. Above 80% relative humidity, hygroscopic growth in terms of an increase of particle diameter and a slight decrease of the index of refraction (real and imaginary part) has been found. Values of the single scattering albedo around 0.9 both at 355 nm and 532 nm indicate some absorption by the aerosol. Values of the lidar ratio are around 26 sr for 355 nm and around 50 sr for 532 nm, almost independent of the relative humidity. Further, data from the photometer and surface radiation values from the local baseline surface radiation network (BSRN) have been applied to derive the radiative impact of the biomass burning event purely from observational data by comparison with a clear background day. We found a strong cooling for the visible radiation and a slight warming in the infra-red. The net aerosol forcing, derived by comparison with a clear background day purely from observational data, obtained a value of –95 W/m 2 per unit AOD500.